2013
DOI: 10.3892/mmr.2013.1622
|View full text |Cite
|
Sign up to set email alerts
|

Pravastatin slows the progression of heart failure by inhibiting the c-Jun N-terminal kinase-mediated intrinsic apoptotic signaling pathway

Abstract: Abstract. Tumor necrosis factor-α (TNF-α) and c-Jun N-terminal kinases (JNKs) are known to be associated with apoptosis and are important in cardiac remodeling. It remains to be determined whether statins inhibit cardiac remodeling through interfering with TNF-α-JNK-related signaling pathways. This study was designed to investigate the effect of pravastatin on the progression of hypertrophy to heart failure in transverse aortic constriction (TAC) and the associations with TNF-α-JNK signaling. Either pravastati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…The mitochondrial matrix protease CLPP plays a central role in the activation of the UPRmt, 10.3389/fcvm.2022.945142 deletion of CLPP in heart increased the synthesis of oxidative phosphorylation subunits and attenuated the mitochondrial cardiomyopathy (91). Cao et al showed that parvostatin improved left ventricular function and slowed the progression of heart failure in mice by blocking UPRmt activator c-Jun (92). The contradictory effects of UPRmt on heart may due to its intensive degree.…”
Section: Dysregulation Of Mitochondrial Proteostasis In Heart Failurementioning
confidence: 99%
“…The mitochondrial matrix protease CLPP plays a central role in the activation of the UPRmt, 10.3389/fcvm.2022.945142 deletion of CLPP in heart increased the synthesis of oxidative phosphorylation subunits and attenuated the mitochondrial cardiomyopathy (91). Cao et al showed that parvostatin improved left ventricular function and slowed the progression of heart failure in mice by blocking UPRmt activator c-Jun (92). The contradictory effects of UPRmt on heart may due to its intensive degree.…”
Section: Dysregulation Of Mitochondrial Proteostasis In Heart Failurementioning
confidence: 99%
“…For example, atorvastatin could attenuate myocardial hypertrophy and remodeling in spontaneously hypertensive rats by inhibiting apoptosis and reversing mitochondrial metabolism via C/EBPβ/ PGC-1α/UCP3 signaling pathway [43]. Moreover, pravastatin attenuated cardiac remodeling via inhibiting JNKdependent pro-apoptotic signaling [44].…”
Section: Lowering Serum Lipids Improves Heart Functionmentioning
confidence: 99%
“…Abundant evidence supports an important role for MAPK in mediating cell apoptosis through the activation of apoptosis-related genes (30)(31)(32)(33)(34)(35). More importantly, it was reported that MAPK activation is mediated by sublytic C5b-9 stimulation (36,37).…”
mentioning
confidence: 99%